Antiviral Therapy for Chronic HBV Infection With Persistently Normal Alanine Aminotransferase: Controversy and Consensus - Zhou, Jing; Wang, Fa-Da; Wang, Meng-Lan; Tao, Ya-Chao; Wu, Dong-Bo; Sheng, Yun-Jian; Xiao, Gui-Bao; Chen, Xue-Bin; Chen, Xin; Chen, En-Qiang (Frontiers in Medicine, 2021)
ALT is one of the most sensitive biochemical indexes to reflect liver injury. It is generally believed that hepatitis B virus (HBV) infected patients with normal ALT levels are in either immune tolerance or low replication stage of the natural history of hepatitis B, and there is no or only mild inflammation in liver tissue, so antiviral therapy is not recommended. However, chronic HBV-infected patients with normal ALT levels are not always in a stable state. A considerable number of patients will develop active hepatitis or occult progress to liver fibrosis, cirrhosis, and hepatocellular carcinoma. Therefore, whether antiviral therapy should be recommended for chronic HBV infection with normal ALT level has been a hot topic in clinical practice. In this paper, the definition of immune tolerance, the relationship between ALT and liver inflammation, and the benefits of antiviral therapy were reviewed, and we hope it will be helpful for clinicians to have a deeper understanding of whether antiviral therapy should be considered for chronic HBV infection with normal ALT.